Talent management and generation z: A systematic literature review through the lens of employer branding - Jorge da Vieira; Carla Gomes Costa; Vasco Santos (Administrative Sciences, 2024)
Generation Z is arriving on the labour scene. In the near future, this generation will dominate organisations' recruitment and selection processes. Theories regarding the attraction and retention of talent were initially developed based on the characteristics of previous generations in the late 20th century. This study aimed to conduct the first comprehensive literature review focused on identifying the attributes of attracting and retaining Generation Z talent. The findings will allow for the identification of the most significant attributes within the examined context. However, certain gaps were uncovered, such as the limited availability of publications explaining the applicability of the conventional theory of attracting and retaining talent to Generation Z natives. Significant lines of research are also suggested for the future.
Keywords: 350; employer brand; employer branding; generation Z; talent recruitment; talent retention